Penerapan Batuk Efektif Dan Fisioterapi Pada Ibu I Dengan Tuberculosis Paru Dalam Meningkatkan Jalan Napas - Nurul Fadhilah; Rina Puspita Sari; M. Hasan Basri; Alfika Safitri (STIKes Ibnu Sina Ajibarang, 2023)
Health problems that often occur at the developmental stage with old age include infectious diseases such as pulmonary TB due to decreased immune system in the elderly. This can be due to the presence of family members who have a history of pulmonary TB disease, lack of understanding regarding prevention of transmission of pulmonary TB disease and in the elderly who are active smokers. The World Health Organization (WHO) states that in 2020 1.5 million people will die from pulmonary TB which makes pulmonary TB the 13th largest cause of death in the world. The large number of TB cases that occur in Indonesia are due to various factors including the home environment, the home environment with insufficient lighting, humidity and poor ventilation of the house which is a breeding ground for tuberculosis bacteria. Method: Case study by providing nursing care to the family of Mr. B especially Mrs. I by doing chest physiotherapy and effective coughing for 5 days. Results and Conclusions: The problem of ineffective airway clearance is resolved with chest physiotherapy and an effective cough which is characterized, the respiratory rate has improved, namely 19x/m, is no longer congested, the secretions are white and slimy, the amount has decreased. Patient can cough effectively, inspection: symmetrical chest movements, palpation: no lumps in the chest, percussion: sonor, auscultation: vesicular. BP : 130/90 mmhg mmHg N : 93x/m.